A legitimidade do poder de jurisdição na construção dos precedentes e o acesso à justiça: fundamentos para uma abordagem democrática do Instituto de Resolução de Demandas Repetitivas (IRDR) - Gabriel, Bruno Cristian (2025)
The main objective of this thesis was to analyze the representativeness of the Incident of Resolution of Repetitive Demands, from the democratic perspective of the principle of access to justice and the democratic legitimacy of jurisdictional power. Access to justice is provided for in the Federal Constitution and is a fundamental principle for the guarantees and enforcement of fundamental rights and must be observed in the analysis of procedural instruments. Likewise, the democratic legitimacy of the jurisdiction is related to the compliance of judges with the Constitutional Charter and their duty to protect fundamental rights. The legitimacy of the Judiciary emanates from the people, who are the source and recipient of the power of the State. The Incident of Resolution of Repetitive Demands comprises a set of procedural institutes implemented by the changes promoted in the Code of Civil Procedure, in the year 2015, which seeks to promote speed in the provision of jurisdiction and uniformity in jurisprudence. This institute is applicable in case of repetition of processes that contain controversy on the same issue solely of law, avoiding conflicting decisions. Based on a bibliographical survey on the subject and an analysis of the case law of the Court of Justice of São Paulo in relation to the incident, the representativeness of this procedural instrument is analyzed critically, since it imposes obstacles to the democratization of access to justice and undermines the democratic legitimacy of jurisdiction. This research investigates whether the democratization of access to justice and the democratic legitimacy of jurisdiction are compromised by the incident procedure, as well as whether there is due and adequate representation of the individuals under the jurisdiction in the decided incident. The hypothesis is that there are obstacles to access to justice in the use of the incident, so that the institute does not exhaust its democratic and civic potential within the scope of the São Paulo court. The conclusion is that there is a need to improve the representativeness of the Incident for Resolution of Repetitive Demands so that it can be a functional instrument for the constitutional commitments to promote social justice